2022
DOI: 10.1021/acs.jpclett.2c03508
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient White Emission from Semiconductor Ink Based on Copper Iodide Nanoclusters

Abstract: Recent developments in the perovskite field have aimed at exploring cluster-based organic–inorganic copper­(I) halides as novel luminescent materials because of their low toxicity and structural diversity. However, the poor framework stability and low dispersion in solvent constitute the key challenges to their practical applications such as luminescent inks. Herein, we report the preparation of highly luminescent inks via one-pot solution synthesis, which consisted of ionic Cu m I n clusters (tetrabutylammon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…From a bonding perspective, the above class of materials is composed of covalently bonded charge-neutral moieties, and their ionic counterparts, namely, organic–inorganic hybrid Cu­(I) halides, also exist. Driven by the thrust of lead-free studies to replace (MA)­PbI 3 (MA = methylammonium) perovskite, enormous interest is shown on this latter type of materials. , Not only do these materials exhibit comparable performance in the above research area but they also complement Cu­(I) halide complexes in the fields of single-component white-light-emitting diodes (WLEDs) and X-ray detection and imaging applications. …”
Section: Introductionmentioning
confidence: 99%
“…From a bonding perspective, the above class of materials is composed of covalently bonded charge-neutral moieties, and their ionic counterparts, namely, organic–inorganic hybrid Cu­(I) halides, also exist. Driven by the thrust of lead-free studies to replace (MA)­PbI 3 (MA = methylammonium) perovskite, enormous interest is shown on this latter type of materials. , Not only do these materials exhibit comparable performance in the above research area but they also complement Cu­(I) halide complexes in the fields of single-component white-light-emitting diodes (WLEDs) and X-ray detection and imaging applications. …”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22][23] Among the different metals employed for the synthesis of nanoclusters, copper shows significant promise over other counterparts such as gold and silver, due to its cost-effectiveness and abundant availability. [24][25][26] Herein, we present the chiral enantiomeric detection of lysine utilizing a pair of optically active copper clusters.…”
Section: Introductionmentioning
confidence: 99%
“…The alterations in chiral absorption efficiency as well as emission profile arising due to the surface modification can be leveraged for sensing purposes 19–23 . Among the different metals employed for the synthesis of nanoclusters, copper shows significant promise over other counterparts such as gold and silver, due to its cost‐effectiveness and abundant availability 24–26 . Herein, we present the chiral enantiomeric detection of lysine utilizing a pair of optically active copper clusters.…”
Section: Introductionmentioning
confidence: 99%
“…Poly-(vinylpyrrolidone) (PVP), a highly affined polymer, has been introduced to prepare cluster inks. 42,47,48 Here we utilized PVP as an auxiliary additive that can effectively limit the crystal growth rate and increase the colloidal stability. The small and regular colloidal Cu 4 I 4 (bzpy) 4 microcrystals with a hexagonal shape and Cu 4 I 4 (tbpy) 4 microcrystals with a rhombic shape were synthesized with PVP assistance (Figures 2a,b and S8).…”
mentioning
confidence: 99%
“…Moreover, the grinding process can induce mechanical stress, which easily leads to cluster isomerization and compromises the original optical properties of the cluster. , To address this issue, we directly synthesized colloidal cluster microcrystals with a uniform size distribution. Poly­(vinylpyrrolidone) (PVP), a highly affined polymer, has been introduced to prepare cluster inks. ,, Here we utilized PVP as an auxiliary additive that can effectively limit the crystal growth rate and increase the colloidal stability. The small and regular colloidal Cu 4 I 4 (bzpy) 4 microcrystals with a hexagonal shape and Cu 4 I 4 (tbpy) 4 microcrystals with a rhombic shape were synthesized with PVP assistance (Figures a,b and S8).…”
mentioning
confidence: 99%